The effects of magnesium administration on cardiac ventricular function, heart rate variability, and myocardial morphological changes in a chronic diabetes disease model in rats - Aboalgasm, Hamida (Department of Human Biology, 2019)
Introduction: Diabetes mellitus (DM) is a leading cause of morbidity and mortality all over the world, and the main cause of the mortality is cardiovascular complications. Such diabetic cardiovascular complications include coronary heart disease, cardiac autonomic neuropathy and ventricular dysfunction. Furthermore, DM is associated with electrolyte disturbances such as those involving potassium, calcium and magnesium (Mg2+). Among these electrolyte disturbances hypomagnesemia is common in diabetes and is associated with increased cardiovascular risk. Recent evidence has shown that Mg2+ supplementation can prevent cardiac autonomic dysfunction and improve ventricular compliance in acute DM. However, the underlying mechanisms of Mg2+ action and Mg2+ effects in chronic DM are unknown. Therefore, the present study explored the effects of Mg2+ administration and its possible mechanisms of action in chronic streptozotocin (STZ) induced diabetic rats. Methods: Adult male Wistar rats were injected intraperitoneally (i.p) once with either STZ (50 mg/Kg body weight) or the STZ vehicle (citrate buffer). The rats were then injected i.p once daily with either magnesium sulphate (MgSO4; 270 mg/Kg body weight) or the MgSO4 vehicle (normal saline) for 28 consecutive days. Blood glucose and body weight were measured throughout the period of the study. On day 28 of the experiments, in-vivo heart rate variability (HRV) parameters were measured to assess cardiac autonomic function using tail pulse plethysmography. Orthostatic stress was induced by tilting the animals from flat position to 70° head-up position. Ex-vivo hemodynamic and electrocardiograph (ECG) measurements were performed on a Langendorff perfusion system. Histological studies of ventricular tissue were performed using haematoxylin-eosin and Masson’s trichrome staining. Western blot analyses of the cardiac autonomic presynaptic marker (synaptophysin) and of the mitochondrial marker of oxidative stress (ATP5A) were performed on right atrial tissue. Plasma Mg2+ concentration was measured using automated photometric assays. Results: STZ treatment significantly increased the blood glucose level and decreased the body weight, and these STZ effects were not prevented by Mg2+ treatment. Diabetes decreased the root mean square differences of successive normal-to-normal intervals (RMSSD) and increased the low frequency (LF) /high frequency (HF) power ratio, which are both indicative of abnormal HRV. These diabetes effects on HRV parameters were significantly prevented by Mg2+ treatments (P < 0.05, STZ+Mg vs. STZ). DM also reduced both the heart rate and orthostatic stress-induced tachycardia, and these effects were reversed by Mg2+ treatment (P < 0.05, STZ+Mg vs. STZ). DM also decreased the left ventricular (LV) developed pressure and the maximal rate of LV pressure increase (+dP/dt), and these diabetic effects were prevented by Mg2+ treatment (P < 0.05, STZ+Mg vs. STZ). DM also decreased the maximal rate of LV pressure decline (-dP/dt) and the rate pressure product, but these parameters were not improved by Mg2+ treatment. DM and Mg2+ treatment did not affect the ECG waveforms and the coronary flow rate in all groups. Histologically, there were no differences in ventricular cardiomyocyte width or in the extent of interstitial fibrosis in all groups. Western blot analysis qualitatively showed a decrease in the expression of synaptophysin in DM that was prevented by Mg2+ treatment. Neither DM nor Mg2+ treatment altered ATP5A expression. The plasma Mg2+ concentration was not altered by DM or Mg2+ treatment. Conclusion: This study showed that Mg2+ treatment prevented cardiac autonomic dysfunction and improved hemodynamic function impairment in chronic DM. Based on the expression of synaptophysin, the mechanism through which Mg2+ improved cardiac autonomic function could involve the prevention of synaptic degradation in diabetes. The effects of Mg2+ on hemodynamic impairment in diabetes seemed to be unrelated to the Mg2+ effects on the cardiac histological structure or on the changes in coronary perfusion. Moreover, the overall effects of Mg2+ in diabetes were independent of its effects on the blood glucose level or the alteration of plasma Mg2+ level. Thus, Mg2+ treatment may have long-lasting therapeutic effects on ventricular dysfunction and cardiac autonomic impairment in chronic diabetes, but further studies are needed to explore the precise underlying mechanisms.